1948
DOI: 10.1104/pp.23.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutrient Level on the Growth and Chemical Composition of Sweetpotatoes in Sand Cultures

Abstract: The present study was undertaken to determine the genieral nutrient requirements of the sweetpotato since field fertilizer tests have yielded a variety of responses with different fertilizer treatments. Sweetpotatoes usually respond to small applications of nitrogen fertilizers but excessive fertility often results in too much vine growth and few storage roots.The study to be reported was conducted on the influence of three or more concentrations of the following chemicals upon vine growth, storage root produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1949
1949
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, the benefits of F. albida are perceived by both men and women as limited to maize, which is a crop controlled entirely by men. The trees are believed to be detrimental to yield of sweet potato roots, which form a major portion of women's marketable produce, perhaps because of negative influence that moderate levels of soil nitrogen have on sweet potatoes (Leonard et al 1948, Hartemink et al 2000. Strong cultural injunctions against cutting F. albida make the trees a permanent fixture on the landscape, and may therefore designate a field for long-term growth of maize.…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of F. albida are perceived by both men and women as limited to maize, which is a crop controlled entirely by men. The trees are believed to be detrimental to yield of sweet potato roots, which form a major portion of women's marketable produce, perhaps because of negative influence that moderate levels of soil nitrogen have on sweet potatoes (Leonard et al 1948, Hartemink et al 2000. Strong cultural injunctions against cutting F. albida make the trees a permanent fixture on the landscape, and may therefore designate a field for long-term growth of maize.…”
Section: Discussionmentioning
confidence: 99%
“…Modem high density plantings require careful management in order to control tree size and maintain productivity. Summer pruning is presently being promoted by some pomologists as an aid to control tree vigor (2,5,10,12,15), to increase fruit bud formation (5,10,11,12), and to improve fruit quality (3,4). Earlier research indicated summer pruning was too devitalizing and laborious to be of commercial value (1).…”
Section: Methodsmentioning
confidence: 99%
“…The carbohydrate content was not changed using var ious ratios of N -P -K (14). Leonard et al (12) observed that carbohydrate content of 'Triumph' sweet potatoes decreased with increased K-levels. Nutrient ratios and various soil amendment applications did not influence the carotene content of sweet pottoes (2,3,5,9,20).…”
mentioning
confidence: 97%
“…Increasing soil organic N levels through the utilization of leguminous cover crops depresses the response of sweet potatoes to N fertilization (20,23). Sweet potato yields consistently increase with N fertilization in sand culture studies (13,21) and in soils of marginal fertility (9). Residual soil N may explain some of the variation among rate-of-response studies conducted in the field.…”
mentioning
confidence: 99%